Market Provisioning of Technology-Enabled Agricultural Services In India - Krishnaswamy, Karunakaran (World Bank, Washington, DC, 2020)
Farmers in India, especially smallholders, face a number of challenges that make their income streams low and unreliable. Start-up companies have entered the agriculture sector with a fee-based revenue model alongside leading technology firms like Microsoft, IBM and Google. Armed with technology, data analytics capabilities and risk capital, these agritech firms provide a range of services to farmers from input sales and conventional cropping advisories, to hiring out farm implements and sales. For farmer collectives and for institutional buyers, farm Enterprise Resource Planning software are being used for automation across the value chain and for traceability. Finally, some forecast weather, pest and disease attacks and yield and loss estimates, automate optimal irrigation and provide intelligence on borrowers' creditworthiness and claims payouts to banks and insurers. There are around 450 agritech firms in India today; of these 35 were started in 2018 alone. Venture capital is rapidly increasing, and total investments jumped up from US$73 million in 2018 to US$248 million in 2019. This note explains the services offered by these firms and provides a perspective on these services based on experiences in World Bank projects and stakeholder interviews.